A root cause failure analysis of coal dust explosion disaster – Gaps and lessons learnt. (April 2020) - Bhattacharjee, R.M.; Dash, A.K.; Paul, P.S.
Highlights: This research paper analysed a 2010 disaster due to explosion that occurred at an underground coal mine in India. Old mine fire, accumulation of flammable gas and deposition of coal dust caused the explosion as a result 14 persons were killed and 5 persons were seriously injured. Thrust is given in this article for identification of root causes like organizational factors, task conditions, task environment etc. which resulted in human error or an unsafe act leading to failure of the defenses and thereby causing the accident/incident. Gaps in the existing accident investigation system of the Indian mining industry were also highlighted. Abstract: Workplace accidents are mostly the result of a combined effect of unsafe acts and unsafe conditions which cause ultimate failure of the existing defenses in the system. The unsafe act or unsafe conditions, task environment and task conditions are the product of some dormant, passive and latent causes generated from the organizational factors. But in accident prevention strategy at the workplace, the major thrust is often put on human behavior behind the unsafe acts. In this paper, an in-depth analysis of a mining disaster in India, as to "Why" and "How" the accident did happen has been carried out and the sequence of events was shown by an Event Sequence Diagram. In this article, efforts have been made to identify the root causes of this accident using an accident causation model like the Accident Causation Tree (ACT) and the Swiss Cheese Model, thereby improving the understanding of the mechanism of the accident. The most important aspect of accident analysis, i.e. the key lessons learned from this accident, has also been identified for the benefit of the industry.